2013
DOI: 10.1074/jbc.m112.426767
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Vesicle Tethering at the Golgi by the Conserved Oligomeric Golgi (COG) Complex and the Golgin TATA Element Modulatory Factor (TMF)

Abstract: Background: Delivery of the vesicle into the pre-fusion state during tethering is not understood. Results: Interactions between the COG complex, golgins and Rabs were mapped. Two ends of the golgin TMF both bind COG and different Rabs, the middle binds the target membrane. Conclusion: COG may reel the vesicle into docking along the golgin. Significance: Mechanistic link between tethering complex and coiled tether established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 67 publications
7
97
0
Order By: Relevance
“…TMF was previously shown to be involved in vesicle tethering by bringing vesicle and target membranes into close apposition before fusion (14). Using TEM analysis on colon sections from WT and TMF −/− mice, we found that mucus-packed granules in goblet cells of TMF −/− mice do not fuse before mucus secretion, as is seen in WT mice, but, rather, are discharged of their cargo late in the secretion stage.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…TMF was previously shown to be involved in vesicle tethering by bringing vesicle and target membranes into close apposition before fusion (14). Using TEM analysis on colon sections from WT and TMF −/− mice, we found that mucus-packed granules in goblet cells of TMF −/− mice do not fuse before mucus secretion, as is seen in WT mice, but, rather, are discharged of their cargo late in the secretion stage.…”
Section: Discussionmentioning
confidence: 92%
“…Tata Element Modulatory Factor (TMF/ARA160; TMF) is a Golgi-associated protein that is apically expressed in colonic enterocytes and goblet cells and has been shown to be involved in vesicle tethering to target membranes (13,14). We recently showed that KO mice lacking TMF/ARA160 (TMF −/− ) have a thicker, more robust colonic mucus layer, which significantly reduces adherent bacterial load and protects the animals from experimental acute colitis (13).…”
mentioning
confidence: 99%
“…In yeast, the COG complex coordinates retrograde Golgi traffic and interacts with RAB, SNARE, and golgin proteins (reviewed in (88,91,92)). In plants, homologues of the COG complex have been predicted on the basis of sequence similarly (93), but there is little experimental evidence for the function and location of this complex in A. thaliana.…”
Section: The Yfp-got1 Enrichment Is Consistent With Previously Publismentioning
confidence: 99%
“…Tethering can be mediated through direct interaction with the coat or through factors, such as SNAREs and Rab GTPases (Cai et al, 2007). Various tethers that mediate intraGolgi trafficking, such as p115 (Uso1) (Guo et al, 2008), the trafficking protein particle II (TRAPPII) complex (Yamasaki et al, 2009) and the conserved oligomeric Golgi (COG) complex (Miller et al, 2013) have been shown to bind the COPI coat. By recognizing specific elements that confer identity to these coated vesicles, possibly in combinations that allow for coincidence detection, these tethers target distinct types of COPI-coated vesicle for fusion with specific cisternae within the Golgi (Malsam et al, 2005).…”
Section: Uncoating Of Copi-coated Vesiclesmentioning
confidence: 99%